Pembelajaran Kooperatif Model TGT untuk Meningkatkan Hasil Belajar Bahasa Inggris Siswa Kelas VIII.A SMP Negeri 6 Mataram - Windrawati, Ni Ketut Ayu (MASALIQ, 2023)
The purpose of this classroom action research is: to find out the increase in English learning achievement through the TGT Cooperative Learning Model for Class VIII.A Students of SMP Negeri 6 Mataram in the Academic Year 2021/2022. This study uses action research (action research) as much as two cycles. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study was students of Class VIII.A SMP Negeri 6 Mataram with a total of 34 students consisting of 16 boys and 18 girls. Based on all the discussion and analysis that has been carried out, it can be concluded that: By applying the Teams Games Tournament (TGT) cooperative learning model, it can be seen that student learning outcomes in the English subject of narrative text material in class VIII.A of SMP Negeri 6 Mataram have increased. After carrying out several cycles the results obtained using the Teams Games Tournament (TGT) cooperative learning model appear to have increased compared to before using it, namely in the pre-action of 84.44 with students completing 67.65%, in cycle I the average value to 84.71, students who completed as many as 27 students 79.41%, student learning outcomes in cycle II with an average value increased to 87.26, students who completed as many as 34 students 100%.